Angry caciques: intrasexual aggression in a Neotropical colonial blackbird. Issue 3 (4th May 2019) - Diniz, Pedro; Oliveira, Rayane S.; Marini, Miguel Â.; Duca, Charles
Abstract : Intraspecific aggressive behavior usually mediates competition for breeding and non-breeding resources among females and for mating opportunities among males. Variation in intrasexual aggressive levels across social and breeding contexts might then differ between sexes or converge due to different reasons. We studied three colonies of the polygynous Red-rumped cacique ( Cacicus haemorrhous ) during one breeding season. We evaluated whether the frequency of female-female and male-male aggressive interactions (number of interactions corrected by total number of individuals of the focal sex) varied with social context (total number of individuals of each sex in the colony) and breeding stage (number of nests under construction and nests with offspring) at each colony. We also tested for the occurrence (linearity and steepness) of a dominance hierarchy among banded males in one colony. We predicted positive correlations between female-female aggression and nests under construction (i.e. competition for nest sites) and between male-male aggression and nests under construction (a proxy for fertile females) and also male-male aggression and number of males (i.e. disputes for dominance rank) in the colony. We observed 533 female-female and 608 male-male aggressive interactions. Female-female aggressive interactions increased with the number of nests under construction in the colony, and decreased during incubation and nestling stages. Male-male aggressive interactions increased with the number of nests under construction, but not with the number of males in the colony. However, we found a steep and linear dominance hierarchy among males shaped by aggressive interactions. Our results suggest that (i) females behave aggressively when competing during the nest-building stage, probably for nest sites and materials; and (ii) male aggression determines the dominance hierarchy and is related to mating opportunities. HIGHLIGHTS ● We observed intrasexual aggressive interactions across breeding stages in a blackbird with female-only parental care.● Female-female and male-male aggressive interactions increased when nests were under construction in the colony.● Dominance hierarchy was evaluated for males and it was linear and steep.● Results suggest females compete for nest sites and male aggression shapes dominance and is associated with mating opportunities.